Óleos funcionais a base de mamona e de casca de castanha de caju na dieta de ovinos - Michailoff, Andressa Alaine (2017)
The objective of this study was to evaluate the effect of the inclusion of different levels of functional oils extracted from castor bean (Ricinus communis L.) and cashew nuts (Anacardium occidentale L.) on nutrient intake and digestibility, ruminal parameters and microbial protein synthesis in sheep. Four male, castrated, undefined, rumen fistulated sheep were used, with a mean live weight of 49,1 kg in a 4 x 4 Latin square experimental design, with treatments being included of 2, 4 and 6 g/animal/day of functional oils and the control treatment without the addition of the oil. After 21 days for adaptation of the animals, the experiment was conducted in four periods of 20 days, 15 for adaptation to diet and five for collection of samples and data. The apparent digestibility of dietary components and ruminal parameters: ammonia, total sugars, peptides and amino acids were not influenced by the treatments. The pH had a cubic effect with higher values observed with supplementation of 4,7 g/day and the lowest value with 1,4g/day of functional oils. Throughout the day, the concentration of sugars presented quadratic effect increasing in the first hours after the feeding. There was a linear effect over time for the concentrations of peptides in the ruminal fluid of sheep receiving 2g/day of functional oils, for amino acid concentrations in sheep not supplemented with functional oils and for ammonia, in this same treatment with a variation of 9,85mg/dL to 25,29mg/dL. In the same way, the ruminal pH also varied as a function of time in a linear way after feeding for all levels of supplementation, with increase in the two hours after feeding, followed by decreasing for at least 6 hours, and evidencing a lower pH value of 5,78. No changes were observed in nitrogen consumption and nitrogen balance, with mean values of nitrogen retained of 24,5g/day, corresponding to 65,07% of the ingested nitrogen. Excreted purine derivatives corresponded to the proportion of 51% allantoin and 48% uric acid, xanthine and hypoxanthine and did not show changes in microbial synthesis.